NILAI-NILAI ANTI KEKERASAN DALAM DUNIA PENDIDIKAN PADA ANAK MELALUI PERMAINAN TRADISIONAL ANGKET-ANGKET PERIUK - Zuhdiyah, Zuhdiyah (PAI RAFAH, 2023)
Traditional games are one of the strategies for strengthening anti-violence values in children. One type of traditional game from Palembang that is rare to be played by children and used as the object of study in this research is the Angket-angket Periuk game. This study aims to describe the form of anti-violence values contained in the traditional game of Angket-angket Periuk and describe the process of forming and strengthening anti-violence values in children through the traditional game of Angket-angket Periuk. This type of research is descriptive qualitative and research data is obtained through interviews and observations. The research population consisted of 8 children aged 6 to 8 years and 9 parents aged over 50 years who lived in the area of seberang Ulu and Seberang Ilir Palembang City. The results obtained from the research are, that there are 6 anti-violence values in the traditional game of questionnaire-pot, namely: sportsmanship value, togetherness value, mutual trust value, fun value, freedom value, and empathy value. The six anti-violence values can be seen and appear when children are about to play, during the game process, and until the children end the game. This study illustrates the strengthening of anti-violence values in children through traditional games from the analysis of respondents. However, further research needs to be done to fully understand the strengthening of anti-violence values in children through traditional games.